Advanced Economic theory : Micro Economic theory. - "Halan, Y.C." (Delhi, 1981)
Economists, wrote Walter Heller, a known economist of Lyndon B. Johnson's time, in his New Dimensions of Political Economy, have in recent times come to play an increasing role in govern ment, and the government is more and more willing to consciously carry out bold economic policies. The effect is that today more than ever it is important for a citizen to understand the economic pro blems of the day and to be able to evaluate the different policies proposed to deal with them. For doing all this the citizen should have a firm grasp of the tools of economic analysis and should be familiar with a wide range of economic concepts.
Keywords: Economic